KAJIAN KESESUAIAN EKOWISATA MANGROVE DI PANTAI PUTRA DELI DESA DENAI KUALA KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Adenia Constansia Sitepu; Yunasfi Djayus; Ahmad Muhtadi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Putra Deli Beach is located in Deli Serdang with an area of approximately 22 ha. This study determine the potential of mangrove ecosystem ecotourism as an object, calculate the suitability and mangrove ecotourism carrying capacity, inventory of facilities and supporting infrastructure in Putra Deli Beach, potential of mangrove obtained by transect measurement of mangrove while the tour suitability obtained by using mangrove ecotourism suitability criteria and supported by interviews with the community and visitors to establish the carrying capacity of the aera and the concept of management. The study was conducted in March until July 2015. The method used was purposive random sampling for potential mangrove and interviews. Samples were taking from three stasiun, stasioin I (located at the West Coast of Putra Deli Beach), station II (located in the middle of Putra Deli Beach) and station III (located in the eastern part of Putra Deli Beach). Mangrove species found include: Avicennia alba, A. lanata, A. marina, Rhizophora mucronata, Bruguiera cylindrica, Acrostichum speciosum, Lumnitzera littorea with population density values exceeding 1000 trees/ha. The mangrove ecotourism suability index at the first station was 71,79% Suitable with Condition, station II was 76,92% Suitable with Condition and station III was 74,35% Suitable with Condition. The carrying capacity (DDK) at first station was 20 persons/day, 24 persons/day at second station and 16 persons/day at third station. The management concept of Putra Deli Beach was definited by the public and controlling by government.Keywords : Ecotourism, Mangrove, Institutioal Patterns, Putra Deli Beach